ANALYSIS OF THE INFLUENCE OF DIGITAL MARKETING: SOCIAL MEDIA MARKETING AS AN EFFORT TO IMPROVE MARKETING METHODS FOR BUSINESS SUSTAINABILITY IN MSMES IN CILODONG DISTRICT - Hertin, Revita Desi; Ahmad Pitra; Hadi Wijaya (Epigram, 2024)
Micro, Small and Medium Enterprises (MSMEs) in Indonesia have made a huge contribution to the nation's economic condition. Digital marketing has brought about world changes, especially in the business world. Some of the issues faced by MSMEs today are in the product marketing process, from several marketing methods that must be maximized because of their huge benefits. This study aims to determine the influence of distance targeting, behavior targeting and content marketing on social media marketing performance and its influence on Business Sustainability in Cilodong District. The research method used is the survey method, using a questionnaire instrument distributed to 50 MSMEs as the target of the research. The determination of the sample in this study uses non-probability sampling, specifically for MSMEs that have used social media marketing. The data analysis process uses SPSS 26 software. The data analysis in this study used multiple linear regression analysis to provide a test for the relationship between hypotheses. The results of the determination coefficient show that digital content, distance targeting, and behavior marketing have a positive effect on social media marketing performance, and social media marketing has a positive effect on Business Sustainability. This research is expected to be able for MSME actors to determine the media in the product marketing process. Future research on social media marketing can be proposed using several other variables and a wider regional reach.